Implementasi Standar Akuntansi Koperasi Simpan Pinjam Sesuai Dengan Permen KUKM Nomor 13 Tahun 2015 : Studi Kasus pada Koperasi Simpan Pinjam Mitra Usaha di Desa Cisempur - M. Ardi Nupi Hasyim; Hanny Novindaning Tyas (Universitas Koperasi Indonesia, 2022)
This study is motivated by problems at Koperasi Simpan Pinjam Mitra Usaha, where financial statements of Koperasi Mitra Usaha are still incomplete in accordance with the Accounting Guidelines of the KUKM Ministerial Regulation Number 13 of 2015 concerning the Accounting Guidelines for Saving and Loans where the preparation and presentation of the financial reporting of savings and loan businesses by cooperatives includes: Balance Sheet, Report on Calculation of Operating Results, Statement of Owner Equity, Statement of Cash Flows, and Notes to Financial Statements. Therefore, in this cooperative, it is necessary to implement financial accounting guidelines to find out how a cooperative complies with the financial standards set by the government.Based on this thing so this study purposes to find out recognition, presentation, and disclosure of financial statements of Koperasi Mitra Usaha in accordance with accounting guidelines with saving and loans businesses.This study uses descriptive qualitative method . the results obtained from this implementation is Koperasi Mitra Usaha can be concluded that they haven’t used the fully recommended cooperative reporting rules as stated in the KUKM Ministerial Regulation No. 13 of 2015 concerning Guidelines for Accounting for Savings and Loans by Cooperatives.